Arab Spring Era: Winds of Change in the Direction of Gender Equality for Tunisian Women. (9th October 2018) - Hitman, Gadi
Abstract: This study asks a simple question: Has there been any upgrading in the status of women in Tunisia in the years following the Jasmine Revolution of December 2010? Based upon a comparative analysis of the Tunisian constitutions of 1959 and 2014, this paper argues that Tunisian women have, in fact, experienced a real change in their status within Tunisian society. Through a combination of their strong collective identity and a self‐initiated process of political opportunity, the popular protest in Tunisia led to legislative changes which were supported by the long history of women's presence in the Tunisian social‐public sphere, together with helpful secular‐oriented political forces. The new constitution of 2014 took steps to attain real gender equality in Tunisia; several Tunisian laws have been changed in favor of women since 2014 as well. The implementation of gender equality has, however, still been too slow and faces obstacles, mainly from Islamist groups — including Salafis who have been exerting pressure to impose a religious character on Tunisian society based upon the Shari'a.